Bioactive compounds from Cudrania tricuspidata: A natural anticancer source. Issue 3 (4th February 2020) - Li, Xusheng; Yao, Zilan; Jiang, Xinwei; Sun, Jianxia; Ran, Guojing; Yang, Xuan; Zhao, Yaqi; Yan, Ying; Chen, Zisheng; Tian, Lingmin; Bai, Weibin
Abstract: The tumor is becoming a critical threat to our lives in these years. Searching for antitumor substances from natural products is a great interest of scientists. Cudrania tricuspidata ( C . tricuspidata ) is a regional plant containing 158 flavonoids and 99 xanthones, and others ingredients with favorable bioactivity. This review comprehensively analyzes the antitumor compounds from C. tricuspidata against different tumors, and 78 flavonoids plus xanthones are considered as underlying antineoplastic. Importantly, the structure of preylation groups is the primary source of antitumor activity among 45 flavonoids plus xanthones, which could be a direction of structural modification for a better antitumor ability. Additionally, the fruits are also preferable sources of antitumor compounds compared to the roots and barks due to the abundant isoflavones and sustainability. However, many studies only focused on the cells viability inhibition of the compounds, the underlying molecular mechanisms, and the intracellular targets remain ambiguous. In conclusion, C . tricuspidata has a great potential for anti-tumor prevention or therapy, but more attention should be paid to deeper research in vitro and in vivo models.